A genome-wide multiphenotypic association analysis identified common candidate genes for subjective well-being, depressive symptoms and neuroticism. (May 2020) - Chu, Xiaomeng; Liu, Li; Wen, Yan; Li, Ping; Cheng, Bolun; Cheng, Shiqiang; Zhang, Lu; Mei ma,; Qi, Xin; Liang, Chujun; Ye, Jing; Kafle, Om Prakash; et al.
Abstract: Subjective well-being (SWB), depressive symptoms, and neuroticism are common and vital traits of mental disorders. Genetic mechanisms of SWB, depressive symptoms and neuroticism remain elusive now. The large-scale GWAS summary datasets of SWB (n = 229, 883), depressive symptoms (n = 180, 866), and neuroticism (n = 170, 911) were obtained from published studies. MASH tool was applied to the GWAS datasets for identifying candidate SNPs shared by SWB, depressive symptoms and neuroticism. SNPs detected by MASH, were then mapped to target genes considering regulatory SNP (rSNP), methylated quantitative trait locus (MeQTL) and the SNPs near to known genes. Gene set enrichment analysis (GSEA) was conducted by the FUMA platform. A total of 122 candidate SNPs were detected by MASH analysis, mapping to 29 target genes, such as CLDN23, MSRA and XKR6. GO enrichment analysis identified multiple immune related gene sets for SWB, depressive symptoms and neuroticism, such as GSE2770_UNTREATED_VS_IL4_TREATED_ACT_CD4_TCELL_48H_DN ( P  = 7.32 × 10 −3 ), GSE6259_FLT3L_INDUCED_DEC205_POS_DC_VS_CD4_TCELL_DN ( P  = 2.52 × 10 −2 ). We also found some mental disorders related gene sets were associated with three phenotypes, such as mood instability ( P  = 1.15 × 10 −6 ) and neuroticism ( P  = 1.72 × 10 −6 ). We identified multiple candidate genes and GO terms shared by SWB, depressive symptoms and neuroticism. Our results support the overlapping genetic mechanisms, and suggest a functional correlation between immunity and SWB, depressive symptoms and neuroticism.